2015
DOI: 10.4162/nrp.2015.9.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E status of 20- to 59-year-old adults living in the Seoul metropolitan area of South Korea

Abstract: BACKGROUND/OBJECTIVESVitamin E is a fat-soluble vitamin and functions primarily as a lipid antioxidant. Inadequate vitamin E status may increase risk of several chronic diseases. Thus, the objectives of this study were to estimate intake and plasma concentration of each tocopherol and to evaluate vitamin E status of Korean adults.SUBJECTS/METHODSThree consecutive 24-h food recalls and fasting blood samples were collected from healthy 20- to 59-y-old adults (33 males and 73 females) living in the Seoul metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…However, the intake is actually inadequate because α-tocopherol only accounts for 22% of total vitamin E intake, while γ-, ɗ-, β-tocopherol accounts for 51.7, 12.6, 1.0%, respectively [10]. Almonds are an excellent source of α-tocopherol providing 7.4 mg per 28 g serving [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the intake is actually inadequate because α-tocopherol only accounts for 22% of total vitamin E intake, while γ-, ɗ-, β-tocopherol accounts for 51.7, 12.6, 1.0%, respectively [10]. Almonds are an excellent source of α-tocopherol providing 7.4 mg per 28 g serving [20].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is synthesized as a result of exposure to solar ultraviolet-B irradiation [ 67 , 68 , 69 ], and the climate conditions of the Valencian Community could compensate this shortage. In the same way, vitamin E, n antioxidant present in the basic food items of the Mediterranean diet such as vegetable oils, nuts and green leafy vegetables [ 70 ], showed deficient intakes for half the study groups, but higher intakes in the overweight category.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that over 20% of the examined people both in developed and developing countries possess plasma a-tocopherol lower than the recommended level (Li et al, 2012). In a study in South Korea, two-third of adults were reported to have suboptimal vitamin-E level and almost one fourth are deficient (Kim and Cho, 2015). About one-third of the pregnant women in rural Nepal are severely affected by vitamin E deficiency (VED) (Jiang et al, 2005).…”
Section: Extent Of Vitamin E Deficiencymentioning
confidence: 99%